IMPROVING LEARNING QUALITY THROUGH THE SYNERGY OF ACADEMIC SUPERVISION, SCHOOL CULTURE, AND TEACHER MOTIVATION - yulianto hery purnomo; ngurah ayu nyoman murniati; muhammad prayito (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the influence of principal academic supervision, school culture, and teacher work motivation on learning quality in public elementary schools in Sedan District, Rembang Regency. Using a quantitative ex post facto design, data were collected from 132 teachers selected through proportional random sampling. Multiple correlation, ANOVA, and multiple regression analyses were employed. The findings reveal that the three independent variables collectively have a very strong and significant effect on learning quality (R = 0.895; R² = 0.800; p < 0.001). Principal academic supervision contributes the most substantially (69.8%), followed by teacher work motivation (68.1%) and school culture (53.1%). These results indicate that learning quality can be significantly improved through an integrated synergy that strengthens instructional supervision, fosters a collaborative school culture, and enhances teachers’ intrinsic motivation. The study highlights the importance of comprehensive managerial interventions in optimizing learning quality and offers empirical evidence for the multidimensional model of supervision–culture–motivation in primary education.